Development of Digital Comic Media Based on Local Wisdom with the Theme of Love Indonesia in Elementary School - Melani Zulfa Hamidah; Linaria Arofatul Ilmi Uswatun Khasanah; Ari Susandi (Jurnal Tematik, 2025)
This study aims to develop digital comic media based on local wisdom that is valid and feasible to use in learning Indonesian in elementary schools. The method used is Research and Development (R&D) with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The research subjects in this study were fifth grade students of SDN 2 Tambakrigadung. The instruments used include media expert validation sheets and material validation sheets as well as student response questionnaires and student activity questionnaires. The results showed: (1) material expert validation obtained an average score of 3.78 which is classified as very valid and media expert validation obtained an average score of 3.83 which is also classified as very valid. (2) the student response questionnaire obtained an average score of 3.61 with a very good category, while the student activity questionnaire obtained an average score of 3.80 with a very good category. Based on these results, it can be concluded that digital comic media based on local wisdom is valid and feasible to use in learning Indonesian in elementary schools.